(3TQM CHjGJ aj GdCdZGR (B((3CHjGJ GdfMh(B)s - (3CHh fUQ GdMSf Hf GSO Hf GdMSf GdaGQbi,J (B487 (3g` s ((3HTjQ Hf CHj HcQ Hf SdjeGf s)
(3ChdgG (B:s
(3HSe Gddg GdQMef GdQMje hGdMeO ddg QH GdYGdejf CeG HYO aEffi CWGd HbGAc MQa GdgeRI bGd YHO Gddg Hf bjS GdQbjGJ s
(3BNQgG (B:s
(3agPg CNdGb GdYdeGA heGShGgG aeWQM eROhd jbhd Hg GdLgGd hfMf fSJYjP HGddg ef gPg GdMGd Je GdcJGH s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B206s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI YGQa MceJ HGdeOjfI GdefhQI s
Keywords: (3GdfMhs